Pengembangan LKPD Tematik pada Tema 4 Subtema 1 Pembelajaran 1 di Kelas V SDN 36 Pontianak Kota - Haliza Rizki; Hery Kresnadi; Suparjan Suparjan; Kartono Kartono; Asmayani Salimi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to produce thematic LKPD products that are valid and practical to use. This research uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data sources in this study were 27 students in class V at SDN 36 Pontianak City. Data collection techniques in this study were interviews, questionnaires and documentation. The product validity research results of thematic LKPD obtained the